The Influence of Social Media Content Experience on Purchase Intention of Electric Vehicle Through Brand Engagement, Brand Awareness, Brand Image, and Brand Attitude - Leo, Fransisco; Berlianto, Margaretha (Jurnal Manajemen, 2026)
This study examines the influence of social media content experience on purchase intention, mediated by brand engagement, brand awareness, brand image, and brand attitude. The five dimensions of content experience investigated include entertainment, customization, interaction, electronic word of mouth (eWOM), and trendiness. A quantitative approach was applied using a structured online survey. A total of 205 respondents were selected through purposive sampling. All respondents were active Instagram users who followed BYD Indonesia's official account. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all five content dimensions significantly influence brand engagement, affecting brand awareness and image. These then shape brand attitude and ultimately impact purchase intention. This study contributes theoretically to digital marketing literature and offers practical implications for electric vehicle brands in optimizing social media content to build stronger consumer-brand relationships.